Tunable assembly of truncated nanocubes by evaporation-driven poor-solvent enrichment - Zhong-Peng Lyu (Lv); Martin Kapuscinski; Lennart Bergström (Stockholm University, 2019)
Raw data of the manuscript entitled "Tunable assembly of truncated nanocubes by evaporation-driven poor-solvent enrichment", including all the SEM (Scanning Electron Microscopy), SAXS (Small-Angle X-ray Scattering) data, OM (Optical Microscopy), photos, SC-XRD patterns (Single-Crystal X-ray Diffraction), TEM (Transmission Electron Microscopy), FTIR (Fourier Transform Infrared Spectroscopy), TG (Thermogravimetry), DLS (Dynamic Light Scattering), Zeta (Zeta Potential Measurement), and apparent size measurement.
Unzip the files with Winzip, WinRAR or 7-Zip.The data is sorted by data type and Figure numbers.The sample ID in the paper was indicated by the file names.
The 2D SAXS data can be managed by DPDAK package (J. Appl. Crystallogr. 47, 1797-1803 (2014).), which can be download from: https://confluence.desy.de/display/DPDAK. For the SEM, TEM, OM, SC-XRD, and photos, simply open them by any photo viewer. The .sfrm files in SC-XRD can be viewed by Bruker XRD Software (https://www.bruker.com/ ).
The .dm3 Digital Micrograph image files in TEM can be opened with Gatan DigitalMicrograph software (http://www.gatan.com/) or with ImageJ from NIH (https://imagej.nih.gov/ij/).
The FTIR, TG, DLS, and Zeta data were in the conventional .txt, .csv format.
For the original source data (as an Excel sheet), please consult the second Reference (to the Associated Publication) below and then click Source Data to download the .xlsx file.
Keywords: 30304 Physical Chemistry of Materials; Physical Chemistry; Fysikalisk kemi